Digitalization and geography education – A curriculum analysis - Peter, Carina; Sprenger, Sandra (ERDKUNDE, 2022)
Digitalization presents many opportunities but also challenges for society. This also entails new tasks for the field of education. This article discusses how geography teaching can contribute to these opportunities and challenges from a subject- and education-specific perspective. To this end, we analyse aspects of subject-specific digitalization and terms associated with digitalization in curricular and framework requirements (n = 57 documents) for different types of schools in every German federal state. We use this to deduce the extent to which the state of subject-specific digitalization is in line with the society’s requirements. In addition, we derive insights into why digitalization is critical to geography education.